On-site mining - Ortiz Sánchez, Oswaldo (2002)
On-site mining is a poorly understood technique for recovering minerals and metal elements from mineral deposits. It comprises methods of dissolving in water and leaching using aqueous chemical compounds that are injected into mineral deposits. There are a large number of minerals that can be recovered by these two methods: By dissolution taking advantage of the solubility in water and the massive form of geological occurrence; by leaching on site using chemical solutions similar to surface leaching. By leaching in situ, metals can be recovered from mineral deposits in which conventional methods of mechanized mining are not applicable due to their low grade, depth of location, dissemination and which have a high degree of natural permeability or artificially created by techniques such as hydrofracturing of the Deposit. In the past it was successfully applied in uranium mineral deposits and experimentally in oxidized copper and free gold deposits. This technique may be developed in the future due to the environmental restrictions introduced in recent years due to the fact that the system does not disturb or pollute nature, it is of low operating cost and low investment in development, equipment and infrastructure, being its two main restrictions. possible contamination of underground aquifers and their low recovery. Other reasons for intensifying the investigation and use of this technique are the tendency of mineral deposits to decrease in grades, quality, size and greater depth of location in such a way that it is far from their economic feasibility of exploitation by conventional methods. This analysis presents the application of the method to a low-grade oxidized copper deposit whose exploitation by traditional methods turns out to be technically and economically not feasible.